Microbial communities in pyrene amended soil–compost mixture and fertilized soil - Adam, Iris K. U. (AMB Express, 2017)
Polycyclic aromatic hydrocarbons are distributed ubiquitously in the environment and form metabolites toxic to most organisms. Organic amendment of PAH contaminated soil with compost and farmyard manure has proven to be efficient for PAH bioremediation mediated by native microorganisms, even though information on the identity of PAH degraders in organic-amended soil is still scarce. Here we provide molecular insight into the bacterial communities in soil amended with compost or farmyard manure for which the degradation mass balances of (13)C-labeled pyrene have been recently published and assess the relevant bacterial genera capable of degrading pyrene as a model PAH. We performed statistical analyses of bacterial genera abundance data based on total DNA and RNA (for comparison) extracted from the soil samples. The results revealed complex pyrene degrading communities with low abundance of individual degraders instead of a limited number of abundant key players. The bacterial degrader communities of the soil-compost mixture and soil fertilized with farmyard manure differed considerably in composition albeit showing similar degradation kinetics. Additional analyses were carried out on enrichment cultures and enabled the reconstruction of several nearly complete genomes, thus allowing to link microcosm and enrichment experiments. However, pyrene mineralizing bacteria enriched from the compost or unfertilized soil-compost samples did not dominate pyrene degradation in the soils. Based on the present findings, evaluations of PAH degrading microorganisms in complex soil mixtures with high organic matter content should not target abundant key degrading species, since the specific degraders may be highly diverse, of low abundance, and masked by high bacterial background. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13568-016-0306-9) contains supplementary material, which is available to authorized users.